2006
DOI: 10.2460/ajvr.67.8.1286
|View full text |Cite
|
Sign up to set email alerts
|

Use of infrared spectroscopy for diagnosis of traumatic arthritis in horses

Abstract: The infrared spectroscopic patterns of fluid from joints with traumatic arthritis differed significantly from the corresponding patterns for controls. These alterations in absorption patterns may be used via an appropriate classification algorithm to differentiate the spectra of affected joints from those of controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 31 publications
1
41
0
Order By: Relevance
“…Duplicate dry films were made for each sample by applying 8-mL aliquots of the diluted serum spread evenly in circular motion into 5-mm wells within a custom-made, adhesive-masked, 96-well silicon microplate. 24 Once the films were thoroughly dried (12 hours at 20uC), the microplate was mounted within a multisampler f interfaced with a Fourier-transform infrared spectrometer equipped with a deuterium tryglycine sulfate detector g to acquire the IR spectra. Absorbance spectra in the IR range of 400-4,000 cm 21 were recorded.…”
Section: Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Duplicate dry films were made for each sample by applying 8-mL aliquots of the diluted serum spread evenly in circular motion into 5-mm wells within a custom-made, adhesive-masked, 96-well silicon microplate. 24 Once the films were thoroughly dried (12 hours at 20uC), the microplate was mounted within a multisampler f interfaced with a Fourier-transform infrared spectrometer equipped with a deuterium tryglycine sulfate detector g to acquire the IR spectra. Absorbance spectra in the IR range of 400-4,000 cm 21 were recorded.…”
Section: Samplesmentioning
confidence: 99%
“…The spectra reflect both the structure of the individual IR active constituents and their relative abundance. 18,22 The absorption patterns within the IR spectra of biological samples may be viewed as biochemical fingerprints that correlate directly with the presence or absence of diseases 18,[22][23][24][25][26] and further provide the basis for the quantitative determination of various serum and urine analytes of diagnostic interest. 18,19,27 We hypothesized that IR spectroscopy of foal sera, with pattern recognition approaches applied to these data, could be used to diagnose FPT and to quantify IgG concentrations.…”
mentioning
confidence: 99%
“…One of the significant advantages of FTIR as a biomarker tool is that the spectra generated from serum or any other body fluid, encompass not only known markers but also unknown markers . Current work has used transmission FTIR that is expensive but more cost effective clinical platforms are being developed …”
Section: Equine Musculoskeletal Biomarkers: Current Knowledge and Futmentioning
confidence: 99%
“…IR spectra derived from synovial fluid of joints with OC were differentiated from controls with an accuracy of 77%, suggesting that this technique may be useful in the diagnosis of OC and to better understand its pathogenesis. A metaanalysis of data generated in recent FTIR studies of samples from control, osteoarthritic and OC-affected joints demonstrated that the IR-based 'fingerprint' for OC has features that distinguish it as unique from that of traumatic OA (Vijarnsorn et al 2006(Vijarnsorn et al , 2007C. Riley, work in progress).…”
Section: Clinical Markers and Treatmentmentioning
confidence: 99%